SEKARANG ATAU NANTI? SEBUAH STUDI MIXED METHODS TENTANG KEPUTUSAN IBU DARI SISWA SMP UNTUK MENGIZINKAN ANAK BERKENDARA SEPEDA MOTOR - Naomi Srie Kusumastutie; Edilburga Wulan Saptandari (Universitas Gunadarma, 2023)
The phenomenon of underage driving closely related to parental consent. This study aimed to describe the dynamics of mothers of junior high school students in giving riding permits to their children. Using the explanatory sequential mixed methods (QUAN-qual), this study was carried out in three phases. Phase 1 was a quantitative study using an online questionnaire, with a total of 496 participants. Data analysis used chi square and Odds Ratio. Phase 2 is a qualitative study. Semi-structured interviews were conducted with three mothers of junior high school students. The results of the interviews were analyzed using thematic analysis. Meanwhile, phase 3 was data integration using joint displays. The findings show that the child’s age is the basis for the mother’s consideration in making the decision to allow the child to drive. In making her decision, the mother primarily considers her husband’s approval, as well as her perception of the benefits, risks, and traffic violations. Environmental and household characteristics play a role in shaping the mother's perception. This study needs to be followed up with the development of parent-based interventions.